How to market budget hotels in Thailand to international people - Pitakanonda, Weetara (2010)
Purpose: The purpose of this research is to suggest how to market budget hotels in Thailand to international people by regarding two main areas, namely the factors controlled by hotels (Marketing mix), and individual aspects of consumer behaviour. Furthermore, another purpose of this paper is to investigate the important aspects needed by international guests in order to provide important information to budget hotel owners to develop their businesses so as to provide the best services to customers and to satisfy their residents.